Effect of disturbed coal pore structure on gas adsorption characteristics: mercury intrusion porosimetry - Liang, Yunpei; Sun, Wanjie; Wu, Zhaopeng; Mao, Shuren; Ran, Qican (Frontiers in Energy Research, 2024)
Studying pore structures of disturbed coal and their influences on adsorption characteristics is conducive to in-depth understanding of occurrence and migration of gas in reservoirs in areas prone to coal and gas outbursts. A mercury porosimeter and a high-pressure gas adsorption instrument were separately used to investigate pore structures and measure adsorption characteristics of disturbed coal and undisturbed coal in Ningtiaota Coal Mine and Xigu Coal Mine (Shaanxi Province, China). In addition, pore structures and gas adsorption characteristics of coal samples were studied. The Menger's sponge model was adopted to calculate fractal dimensions of coal samples, to estimate influences of pore structures and fractal features on the gas adsorption characteristics of disturbed and undisturbed coal.Results show that the pore volume of undisturbed coal is mainly contributed by micropores and transitional pores, while that of disturbed coal arises mainly from macropores and mesopores. Micropores and transitional pores account for large proportions of the specific surface area of pores in both disturbed and undisturbed coal. The adsorption isotherms of disturbed and undisturbed coal conform to the Langmuir equation and tectonism increases the limiting adsorption quantity of coal. The fractal dimensions D1 of the four types of coal samples in the experiments are in the range of 2.7617 to 2.9961, while the fractal dimensions D1 and D2 of disturbed coal are both larger than those of undisturbed coal, indicating that disturbed coal is more likely to collapse under high pressure. The total pore volume, total specific surface area of pores, and fractal dimensions are positively correlated with the adsorption constant a, while they have U-shaped correlations with the adsorption constant b of coal samples. The adsorption constant a of disturbed coal is always greater than that of undisturbed coal, while no obvious trend is observed between the adsorption constant b and tectonism.